RELATIONSHIP OF SALIVA pH AND DMF-T INDEX IN METADON HOUSING THERAPY IN YOGYAKARTA CITY - Hanik Maria; Diyah Fatmasari (Jurnal Riset Kesehatan, 2020)
One of the factors causes dental caries is salivary state. Drug addicts may have different salivary pH due to the drug content that is commonly consumed. The purpose of this study was to determine the relationship of salivary pH to the DMFT index in the Methadone Maintenance Therapy group in the city of Yogyakarta. This type of observational analytic study is Case control design. A sample of 64 subjects, divided into 2 case and control groups. Case groups are people who are members of the Methadone Maintenance Therapy Program at the Gedongtengen Health Center in Yogyakarta. Saliva pH measuring instrument is a pH strip. Test the relationship between salivary pH and DMFT using the Spearman rank test. The results showed that the average DMF-T in the case group was 8.4, higher than the control group 2.1 while the saliva pH of the PTRM group in the acid category (5.8) was lower than the control group with a neutral pH category (6.6). There is a significant relationship between salivary pH and DMF-T index in the Methadone Maintenance Therapy group in Yogyakarta City.